Say "Cheesy!" a feminist analysis of the "unmasculine" male as the "other" in Greenwich's "Cheesy" commercials - Tiongson, Patrick Simon Alejandro 1991- (2013)
"This thesis investigates how Greenwich uses a colloquial term like 'cheesy' in representing masculinities in one of its recent campaigns, the 'Cheesy" commercials series. According to research, the gender category of masculinity can be expressed in several forms, rather than just being tied down to a set of socially prescribed characteristics. There are alternative masculinities that deviate from the norm of hegemonic masculinity: Greenwich, one of the leading pizza brands in the Philippines, uses these alternative masculinities in the portrayal of its male characters in one of its advertising campaigns, the 'Cheesy' commercial series. Moreover, these masculinities are branded with a colloquial word used in today's culture, "cheesy". To understand why Greenwich uses such a term to represent the men in their 'Cheesy' commercials, and what its gendered implications are, this thesis uses the feminist theory of 'othering' and the method of textual analysis. As the research suggests, Greenwich uses the word 'cheesy' as a way of casting out alternative masculinities as the 'other'. In this sense Greenwich helps to maintain and promote the socially accepted values of masculinity."